2021
DOI: 10.1080/09720502.2020.1838061
|View full text |Cite
|
Sign up to set email alerts
|

Juxtaposing inference capabilities of deep neural models over posteroanterior chest radiographs facilitating COVID-19 detection

Abstract: Juxtaposing inference capabilities of deep neural models over posteroanterior chest radiographs facilitating COVID-19 detection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The feature map is diminished by 50 percent, after each pooling layer. The last pooling layer has 7 × 7 with 512 channels [ 32 ], [ 33 ]. The network comprises total of 14, 714, 688 parameters.…”
Section: Methodology and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feature map is diminished by 50 percent, after each pooling layer. The last pooling layer has 7 × 7 with 512 channels [ 32 ], [ 33 ]. The network comprises total of 14, 714, 688 parameters.…”
Section: Methodology and Materialsmentioning
confidence: 99%
“…× 7 with 512 channels[32],[33]. The network comprises total of 14, 714, 688 parameters.VOLUME , 2020…”
mentioning
confidence: 99%
“…They concluded that fewer features yielded better results because of less chances of overfitting and hence used the single feature for analysis. Jee et al [30] studied the inference capabilities of neural network models using chest radiographs for the purpose of Covid detection which showed an accuracy of 98% using CNN. Transfer learning architecture was used by Kermany [25] to diagnose paediatric pneumonia using chest X-rays, moreover differentiate between viral and bacterial pneumonia using 5232 X-ray images further labelled as viral, bacterial and normal.…”
Section: Related Workmentioning
confidence: 99%
“…There are many applications of CNN architectures decoding paddy crop disease detection [25], COVID-19 detection [26], facial recognition [27], and nuclei segmentation [28,29]. CNNs are composed of four main types of layers-convolutional, Maxpooling, flattening, and full connection.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%